The support of the process of training pre-service mathematics teachers by means of cloud services - Vladyslav Ye. Velychko; Elena H. Fedorenko; Nataliia V. Kaidan; Vladimir N. Soloviev; Olga V. Bondarenko (Academy of Cognitive and Natural Sciences, 2021)
The training of pre-service mathematics teachers is a complex process due to the specifics of the field. Informatization of education affects all the areas, and pre-service mathematics teachers can not be left out. The article is devoted to the problem of supporting the process of professional training of pre-service mathematics teachers by means of cloud services. Examples of the use of cloud technologies are given. The analysis of a survey of pre-service mathematics teachers on the use of information and communication technologies in the training process is done.